Analysis of Public Knowledge Regarding Preparedness in Facing Earthquake Disasters: A Literature Review - Farida Nayla Kholillah Ruswan; Syarif, Ahmad (Journal of Diverse Medical Research: Medicosphere, 2024)
Background: Earthquakes are one of the natural disasters that often occur in various countries.In 2023, there were 10,789 earthquakes in Indonesia with 54,652 fatalities. Method: in theform of a literature review by collecting information taken from several journals in the formof primary data. The data obtained came from the PubMed, NCBI, Google Scholar, Mendeley,ResearchGate, and Scopus databases for the last 5 years based on keywords. Purpose: Thisarticle aims to improve community preparedness for earthquake disasters. Results: Educationalcounseling and simulations carried out to foster public understanding of disaster preparednessare the right steps to build public awareness of the importance of disaster preparedness inaccordance with established guidelines. Preparedness as stipulated in Law No. 24/2007concerning Disaster Management is defined as a series of activities carried out to anticipatedisasters through organizing with appropriate and efficient steps. Conclusion: Increasingcommunity capacity through appropriate health promotion will have an impact on the level oflocal community participation in understanding the importance of disaster preparedness,especially earthquakes in the area.Keywords: Disaster, Earthquake, Preparedness, Counseling